A novel tumor-targeting strain of Xenorhabdus stockiae exhibits potent biological activities - Zhang, Chao; Chen, Hanna; Hüttel, Stephan; Hu, Shengbiao; Zhang, Wangyue; Ding, Xuezhi; Yin, Jia; Yin, Yulong; Müller, Rolf; Xia, Liqiu; Zhang, Youming; Tu, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
Xenorhabdus are symbionts of soil entomopathogenic nematodes of the genus Steinernema presenting two distinct forms in their life cycle, and can produce a broad range of bioactive compounds. In this study, a novel Xenorhabdus stockiae strain HN_xs01 was isolated from a soil sample via an entrapment method using Galleria melonella nematodes. The supernatants of strain HN_xs01 exhibited antimicrobial properties against gram-negative and gram-positive bacteria, and insecticidal properties against Helicoverpa armigera larvae, and antitumor properties as well. Moreover, three linear rhabdopeptides (1, 2 and 3) were identified from strain HN_xs01 using nuclear magnetic resonance analysis, which exhibited significant cytotoxic activity against the human epithelial carcinoma cell line A431 and the human chronic myelogenous leukemia cell line K562. Some bacteria have been reported to colonize the tumor region, and we determined that HN_xs01 could grow in tumor xenografts in this study. HN_xs01 invaded and replicated in B16 melanoma cells grafted into C57BL/6 mice, resulting in tumor inhibition. Moreover, strain HN_xs01 not only merely aggregated in the tumor environment, but also prevented pulmonary metastasis. It caused fragmentation of vessels and cell apoptosis, which contributed to its antitumor effect. In conclusion, X. stockiae HN_xs01 is a novel tumor-targeting strain with potential applications in medicinal and agricultural fields.